The 2020 earthquake sequence and seismic hazard scenario of Mizoram state in northeast India - Bansal, Brijesh K.; Sutar, Anup K.; Verma, Mithila (Frontiers in Earth Science, 2022)
The Mizoram state of India lies in close proximity to the active Indo-Burma subduction zone and had experienced several moderate to large earthquakes, including the M7 event in 1938. Since 2015, only two events with 5<M<6 have occurred in the area, however, a sudden enhancement of earthquake activity (M3.0–M5.7) was observed from June to August 2020 in the eastern part of the Mizoram state, including the four events of M ≥ 5.0. We analysed the waveform data of 21 events recorded by the local and regional BBS to estimate the source parameters. The focal depth of these events varies from 13 to 45 km, while other parameters such as corner frequency, source radius, stress drop, and scalar seismic moment of the events are found in the range of 0.45–3.36 Hz, 0.77–5.58 km, 1.3–193 bars, and 3.98107E+13 to 6.30957E+17 Nm, respectively. The seismicity pattern shows two distinct clusters along the well-demarcated faults in the region, and most of them are generated by strike-slip movements. The Churachandpur-Mao Fault (CMF) is found to be the most active tectonic element in the study area. Hence, an M8 event has been simulated on the same fault using the stochastic simulation technique. The technique was validated by simulating the three M+5 events on the same source zone and comparing the simulated PGA, frequency, and response spectrum with the observed data. The simulation reveals that a PGA ∼480 gals is expected near the fault zone. The easternmost districts of Mizoram, such as Champai, Serchhip, Lunglei, Saiha, and Aizawl, may experience severe PGA (250–450 gals). The response spectral acceleration corresponding to single-storey, double-storey, 3–4 storey, and 5–6 storey buildings has also been estimated in the present study and it is found to vary in the range of 1,400–200 gals. The result of the present study will be useful in various engineering applications and help reduce the loss of lives and damage to infrastructure due to future large events in the region.